KEBERADAAN MASJID AGUNG MADANI ISLAMIC CENTER TERHADAP KEHIDUPAN MASYARAKAT DI KABUPATEN ROKAN HULU (2008-2018) - Br. Nasution, Anna Fasiri; Ibrahim, Bedriati; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The Great Mosque of Madani Islamic Center was built based on the idea of the Regent at that time, Mr. Drs. H. Achmad, M.Si, that the mosque was founded because in the Rokan Hulu Regency area there was no representative mosque to serve as a place of prayer and religious activities at the district level. In 2015 the Great Mosque of Madani Islamic Center was awarded as the best mosque in Riau Province. The purposes of this study are 1) To find out the background of the establishment of the Great Mosque of Madani Islamic Center in Pasir Pengaraian Rokan Hulu Regency 2) To find out the function and role of the Great Mosque of Madani Islamic Center on community life in Rokan Hulu Regency 3) To determine the impact of the existence of the Great Mosque of Madani Islamic Center towar life in Rokan Hulu Regency 4) To find out tourists' perceptions of the existence of the Great Mosque of Madani Islamic Center in Rokan Hulu Regency. The method of this research is qualitative and quantitative. The result of this study shows that the existence of the Great Mosque of Madani Islamic Center has a significant impact on the society life in Rokan Hulu in social, economic, educational and religious tourism fields.Key Words: The Great Mosque of Madani Islamic Center, Society Life